2018
DOI: 10.1016/j.metabol.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory liposomes targeting liver macrophages arrest progression of nonalcoholic steatohepatitis

Abstract: , Immunomodulatory liposomes targeting liver macrophages arrest progression of nonalcoholic steatohepatitis, Metabolism (2017Metabolism ( ), doi: 10.1016Metabolism ( /j.metabol.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Pharmacokinetic studies show the preferential uptake of the liposomes by the liver although they accumulate not only in Kupffer cells but also in monocytes, infiltrating macrophages and, to a lesser extent, T cells. Liposomes also induce a repolarization of macrophages to a regulatory phenotype (50,51).…”
Section: Liposomesmentioning
confidence: 99%
“…Pharmacokinetic studies show the preferential uptake of the liposomes by the liver although they accumulate not only in Kupffer cells but also in monocytes, infiltrating macrophages and, to a lesser extent, T cells. Liposomes also induce a repolarization of macrophages to a regulatory phenotype (50,51).…”
Section: Liposomesmentioning
confidence: 99%
“…In this study, liposomes containing curcumin and calcitriol were injected into these diseased mice, and the response by macrophages was assessed. It was found that the macrophages did take up the liposomes, and researchers noticed both an in vivo and in vitro reduction in proinflammatory responses by macrophages [42]. This finding supports the use of liposomes in reducing the inflammatory response by macrophages in diseased animals, which could eventually lead to clinical applications for human disease.…”
Section: Targeting Of Macrophagesmentioning
confidence: 67%
“…Non-alcoholic fatty liver disease, also known as NAFLD, is associated with macrophage inflammation within the liver tissue [42]. In this study, liposomes containing curcumin and calcitriol were injected into these diseased mice, and the response by macrophages was assessed.…”
Section: Targeting Of Macrophagesmentioning
confidence: 99%
“…Several targeted nanoparticle drug-delivery systems have been reported in advanced trial phases for certain cancers 1 and have the potential for the treatment of autoimmune disorders and inflammatory diseases such as nonalcoholic fatty-liver disease (NAFLD). 2,3 Macrophages (Mϕ) are important players in the pathogenesis of, for example, obesity-associated type 2 diabetes, inflammatory diseases such as nonalcoholic steatohepatitis (NASH) and rheumatoid arthritis and in certain cancers. [4][5][6][7] These phagocytes are plastic, heterogenic immune cells capable of adapting, polarizing, and altering cytokine production and cell surface marker expression according to their microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…30 Delivering encapsulated calcitriol to, for example, EGFR tyrosine kinase inhibitor-resistant lung cancer or to Mϕ involved in NASH has demonstrated effective cellular uptake and drug efficacy. 2,31 In the present study, we developed calcitriol lipid nanoparticles (LNP(Cal)) and PEGylated calcitriol lipid nanoparticles (PEG-LNP(Cal)) with a core of triolein-POPC (2-oleoyl-1-palmitoyl-sn-glycero-3-phosphocholine), as reported by Zhigaltsev et al 32 PEG-LNPs have an improved half-life and circulation time in vivo compared to conventional LNPs 1 and are able to avoid rapid uptake by nontarget cells. Several studies have shown that the improved half-life of PEG-LNPs results in the increased accumulation of LNPs in tumor and inflamed areas, where increased presence of immune cells is observed in certain cancers and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%